Sustainable choices: The relationship between adherence to the dietary guidelines and food waste behaviors in Italian families - Federica Grant; Laura Rossi (Frontiers in Nutrition, 2022)
IntroductionFood loss and waste are urgent problems to address. Recent estimates highlighted that the highest quantities of waste are generated at the household level and for this reason, the interest in this sector has increased over years.MethodsTo investigate if there is a connection between consumers’ behaviors aiming at reducing food waste and consumers’ choices in adopting healthy eating habits, a survey among a sample (n = 2,869) representative of the Italian population was carried out with the use of validated questionnaires.ResultsResults demonstrated that the higher the adherence to the Italian dietary guidelines indicator (AIDGI) the higher the score measuring household food waste behaviors (HFWB). In particular, the highest AIDGI corresponds to a preponderance of respondents that was more able to plan the shopping and the use of food (38.9%, p < 0.001), to better evaluate the quantities to cook (40.4%, p < 0.001), to avoid impulsive buying (35.2%, p < 0.01), to have a high knowledge of the food stored (38.4%, p < 0.001), to reuse leftovers (35.4%, p < 0.001), to assess food safety (34.7%, p < 0.001), to plan accurately (34.9%, p < 0.01), to know how to prolong the shelf life of a product (34%, p < 0.05), and to cook creatively (32%, p < 0.01). In addition to that, half of the respondents with the lowest AIDGI score did not receive any education regarding food waste (51.1%, p < 0.001). HFWB indicators globally resulted in scores ranging from 40 to 80% revealing the attention of Italians to food waste issues. Regarding eating habits, in half of the sample (50.4%) a consumption pattern with low adherence to nutritional recommendations was found, in particular among men (34.4%), younger age groups (40%), and people living in large families (42.3%).DiscussionThe overall results provided interesting information that could give input for planning nutrition education actions and identifying targets and topics to be addressed.